The Influence Of The Marketing Mix On Customer Satisfaction At Yamaha Thamrin Brothers Panorama In Bengkulu City - Sarifudin, Asep; Wijaya, Ermy; Effendi , Yanto (Universitas Dehasen Bengkulu, 2023)
Along with the development of an increasingly advanced era, marketing has become an important role in a company. The influence of the marketing mix with product, price, place and promotion variables can be a reference for customer satisfaction provided by Yamaha Thamrin Brothers Panorama in Bengkulu city. The research objective is to determine the effect of product, price, place, and promotion on customer satisfaction at Yamaha Thamrin Brothers Panorama in Bengkulu city. The type of research used is quantitative. The data analysis method used is multiple linear regression. The test results obtained are: 1) Partial test results show that the product (x1) has a significance value of 0.002 <0.05. Price (x2) has a significance value of 0.001 <0.05. Place (x3) has a significance value of 0.002 <0.05. The promotion (x4) has a significance value of 0.003 <0.05. Thus, the results of the t (partial) test show that there is a positive and significant influence of product, price, place, and promotion variables on customer satisfaction at Yamaha Thamrin Brothers Panorama in Bengkulu city. 2) simultaneous test results with a significance requirement of <0.05. Obtained a significance probability number of 0.001 <0.05 means that product, price, place, and promotion simultaneously affect customer satisfaction at Yamaha Thamrin Brothers Panorama in Bengkulu city.